Microwave ablation therapy assisted by artificial pneumothorax and artificial hydrothorax for lung cancer adjacent to the vital organs - Chen, Jian; Qi, Liqin; Chen, Jin; Lin, Qingfeng; Yan, Yuan; Chen, Jie; Lin, Zhengyu (Frontiers in Oncology, 2022)
Objectives: This study aimed to investigate the technical methods and safety of artificial pneumothorax and artificial hydrothorax in the treatment of lung cancer adjacent to vital organs by CT-guided microwave ablation. Subjects and Methods: Three of the six patients were men and three were women, with a mean age of 66.0 years (range 47–78 years). There patients had primary pulmonary adenocarcinoma, one had lung metastasis from liver cancer, one had lung metastasis from colon cancer, and one had lung metastasis from bladder cancer. There were four patients with a single lesion, one with two lesions, and one with three lesions. The nine lesions had a mean diameter of 1.1 cm (range 0.4–1.9). In three patients, the lung cancer was adjacent to the heart, and in the remaining three, it was close to the superior mediastinum. Six patients were diagnosed with lung cancers or lung metastases and received radical treatment with microwave ablation (MWA) assisted by artificial pneumothorax and artificial hydrothorax in our hospital. Postoperative complications were observed and recorded; follow-up was followed to evaluate the therapeutic effect. Results: The artificial pneumothorax and artificial hydrothorax were successfully created in all six patients. A suitable path for ablation needle insertion was also successfully established, and microwave ablation therapy was carried out. 2 patients developed pneumothorax after operation; no serious complications such as operation-related death, hemothorax, air embolism and infection occurred.Moreover, 4–6 weeks later, an enhanced CT re-examination revealed no local recurrence or metastasis, and the rate of complete ablation was 100%. Conclusions: Microwave ablation, assisted by artificial pneumothorax, artificial hydrothorax, is a safe and effective minimally invasive method for treating lung cancer adjacent to the vital organs, and optimizing the path of the ablation needle and broadening the indications of the ablation therapy